KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS TABANAN II TAHUN 2019 - Diantari, Ida Ayu Putu Mita; Sutarga, I Made (ARCHIVE OF COMMUNITY HEALTH; Vol 6 No 2 (2019): Desember 2019DO - 10.24843/ACH.2019.v06.i02.p04, 2019)
ABSTRACT The percentage of deaths from diabetes in Indonesia is the second highest after Sri Lanka. One of the behaviors for controlling diabetes mellitus is adherence with taking madication. Adherence with treatment that can increase risk of complications and the risk of hospitalization. Puskesmas Tabanan II is a health center that has the highest number of type 2 DM patient visits in Tabanan Regency. This study aims to determine the success rate of taking medication in type 2 DM patients in the working area of ??Puskesmas Tabanan II. The research design was descriptive observational using a cross sectional study design to describe medication adherence in type 2 DM patients in the Puskesmas Tabanan II working area in 2019. The sampling technique was a systematic random sampling method. This study use inferential analysis in the form of univariate analysis and bivariate analysis. The sample of this study is type 2 DM patients in the Puskesmas Tabanan II working area. The results of the analysis show that of 69 respondents, 52 respondents (75.36%) were categorized as obedient and 17 respondents (24.64%) were categorized as non-compliant. This is caused by several factors, namely age, sex, level of education, occupation, type of medication consumed, duration of suffering from diabetes, and family support. It is recommended that Puskesmas can increased education regarding the importance of family support to families of type 2 DM patients so that adherence to medication, especially taking medication can be increased. Keywords : Diabetes Mellitus, Adherence with Taking Medication, Family Support